Irradiation for locoregionally recurrent, never‐irradiated oral cavity cancers. Issue 11 (28th August 2014) - Lok, Benjamin H.; Chin, Christine; Riaz, Nadeem; Ho, Felix; Hu, Man; Hong, Julian C.; Shi, Weiji; Zhang, Zhigang; Sherman, Eric; Wong, Richard J.; Morris, Luc G.; Ganly, Ian; et al.
Abstract Background The purpose of this study was to report the clinical outcomes and related prognostic factors of patients who underwent radiotherapy (RT) for the treatment of recurrent, never‐irradiated oral cavity cancer (recurrent OCC). Methods The records of consecutive patients with nonmetastatic recurrent OCC who presented to and were treated with RT at our institution between 1989 and 2011 were reviewed. The Kaplan–Meier method was used to calculate overall survival (OS). The cumulative incidences of disease‐specific death, local failure, regional failure, and distant metastasis were calculated with death as a competing risk. Results One hundred twenty‐three patients were identified. Median follow‐up for living patients was 54 months and 16 months for all patients. Ninety‐one patients had salvage surgery followed by adjuvant RT. Definitive RT was utilized in the remaining 32 patients. The 5‐year OS was 40%. The 5‐year cumulative incidence of disease‐specific death, local failure, regional failure, and distant metastasis was 55%, 34%, 22%, and 20%, respectively. Recurrent T classification and lack of salvage surgery were independently associated with worse disease‐specific death and decreased OS, respectively. Subset analysis of patients who underwent salvage surgery demonstrated that age, recurrent T classification, and perineural invasion (PNI) were independently associated with decreased OS; recurrent T classification and thicker tumors were independently associated with worse disease‐specific death; and positive/close margins and primary T classification were independently associated with increased local failure. Conclusion In this group of patients with recurrent OCC, clinical outcomes were similar or improved when compared with other recurrent OCC‐specific reports. In the salvage surgery subset, tumor thickness and PNI are recurrent pathologic features associated with outcomes that were only previously demonstrated in studies of primary disease. Because of the relatively worse outcomes in patients receiving definitive or adjuvant RT for recurrent OCC, we advocate for the appropriate use of postoperative RT in the initial management of oral cavity cancers. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1633–1641, 2015